Results of radio-frequency catheter ablations in patients with long-standing persistent atrial fibrillation - A. Doronin; M. Meshkova (Ukrainian Journal of Cardiovascular Surgery, 2019)
Catheter treatment outcome in non-paroxysmal forms of atrial fibrillation (AF) is worse than that in paroxysmal forms. The search for optimal methods of AF catheter ablation is ongoing.The objective is to analyze our own experience of radiofrequency catheter ablation in patients with long-standing persistent AF. Material and methods. The article presents the results of radiofrequency catheter ablations of long-standing persistent AF in 47 consecutive patients, who underwent 57 procedures, that is 1.2 procedures per patient. Most procedures were performed using non-irrigated catheters with a 4-mm distal electrode without using navigation systems.Results and discussion. After the first procedure, sinus rhythm was maintained during 1 year in 27 (57.4%) patients. Considering repeated procedures, 35 (74.5%) patients were in sinus rhythm during 1 year, of which 8 (22.9%) patients received antiarrhythmics. After the last procedure it was possible to follow up 42 (89.4%) patients. The mean follow up period was 2.6 ± 1.9 years. Along with it, the sinus rhythm was preserved in 19 (45.2%) patients, 11 (57.9%) of them were on the antiarrhythmic therapy.One (2.1%) patient had typical atrial flutter (AFl), and another one had left-sided AFl, which were ablated during the repeat procedures.The one (1.8%) procedure was complicated with pericardial tamponade, which was immediately resolved by pericardiocentesis.The safety of using non-irrigated ablation catheters with a 4-mm distal electrode was confirmed by a low number of complications, not beyond the limits given in the literature.Thus, this method of catheter ablation is quite effective and safe for long-standing persistent AF.